The role of NLRP3 inflammasome in type 2 inflammation related diseases - Shenming Xu; Dan Wang; Lina Tan; Jianyun Lu (Taylor & Francis Group, 2024)
AbstractType 2 inflammation related diseases, such as atopic dermatitis, asthma, and allergic rhinitis, are diverse and affect multiple systems in the human body. It is common for individuals to have multiple co-existing type 2 inflammation related diseases, which can impose a significant financial and living burden on patients. However, the exact pathogenesis of these diseases is still unclear. The NLRP3 inflammasome is a protein complex composed of the NLRP3 protein, ASC, and Caspase-1, and is activated through various mechanisms, including the NF-κB pathway, ion channels, and lysosomal damage. The NLRP3 inflammasome plays a role in the immune response to pathogens and cellular damage. Recent studies have indicated a strong correlation between the abnormal activation of NLRP3 inflammasome and the onset of type 2 inflammation. Additionally, it has been demonstrated that suppressing NLRP3 expression effectively diminishes the inflammatory response, highlighting its promising therapeutic applications. Therefore, this article reviews the role of NLRP3 inflammasome in the development and therapy of multiple type 2 inflammation related diseases.